1999
DOI: 10.1017/s0033291799008739
|View full text |Cite
|
Sign up to set email alerts
|

Neuroticism and self-esteem as indices of the vulnerability to major depression in women

Abstract: The personality construct of neuroticism is a substantially better index of a woman's underlying vulnerability to major depression than is self-esteem. These findings suggest that overall emotionality or emotional reactivity to the environment reflects risk for depression better than does global self-concept.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
112
1
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 154 publications
(123 citation statements)
references
References 31 publications
8
112
1
2
Order By: Relevance
“…Neuroticism is itself heritable (Jang, Livesley, & Vernon, 1996;Loehlin, McCrae, Costa, & John, 1998), thus possibly accounting for genetic influences on self-esteem level and perceived stability. Past research indicates that self-esteem level shows a genetic correlation with neuroticism (Roberts & Kendler, 1999), although we lack evidence of a similar link with perceived stability. If a shared underlying temperament dimension explained entirely genetic influences on level and perceived stability, we would expect genetic influence on both to be carried by a common genetic factor.…”
contrasting
confidence: 90%
“…Neuroticism is itself heritable (Jang, Livesley, & Vernon, 1996;Loehlin, McCrae, Costa, & John, 1998), thus possibly accounting for genetic influences on self-esteem level and perceived stability. Past research indicates that self-esteem level shows a genetic correlation with neuroticism (Roberts & Kendler, 1999), although we lack evidence of a similar link with perceived stability. If a shared underlying temperament dimension explained entirely genetic influences on level and perceived stability, we would expect genetic influence on both to be carried by a common genetic factor.…”
contrasting
confidence: 90%
“…Data on neuroticism reveal consistently that neuroticism is genetically related to both depression (measured categorically or dimensionally) and anxiety. Although to a lesser extent, there is overlap in unique environmental factors between neuroticism, depression and anxiety (Jardine et al 1984 ;Martin et al 1988;Kendler et al 1993 a ;Gustavsson et al 1996 ;Roberts & Kendler, 1999 ;Boomsma et al 2000 ;Fanous et al 2002 ;Ono et al 2002 ;Stein et al 2002). No study found an influence of common environment and thus, no significant correlation between common environmental factors either.…”
Section: Results and Conclusion From Twin And Family Studiesmentioning
confidence: 97%
“…This association is partly due to pleiotropic genetic influences (Jardine et al, 1984;Kendler et al, 1993;Mackintosh et al, 2006;Middeldorp et al, 2005;2011;Roberts & Kendler, 1999). Genetic pleiotropy also accounts for the association between neuroticism and borderline personality disorder (Distel et al, 2009).…”
mentioning
confidence: 99%